2020
DOI: 10.1093/jaoacint/qsaa105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Bioactive Constituents of Artemisiae argyi Folium Collected at Different Developmental Stages

Abstract: Background Artemisiae argyi Folium has been used as herbal medicine and food supplement in China and other Asian countries. There is no report about whether the different developmental stages can influence the bioactive compositions of Artemisiae argyi Folium. Objective To investigate the dynamic changes of bioactive constituents of Artemisiae argyi Folium collected at different developmental stages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Proximate composition analyses of the three olive tree leaf varieties were performed in triplicate, according to AOAC (2000, 2005, 2006) methods [ 32 , 33 , 34 , 35 ]: dry matter (in an oven at 105 °C to constant weight; P Selecta, Barcelona, Spain); ash (incinerated at 500 °C for 6h in a muffle furnace; Nabertherm B-180, Lilienthal, Germany); protein quantitation via the Kjeldahl method (AOAC, 2000) using a digestor (DK6 digester, Velp Scientific, Usmate, Italy) followed by distillation (Keltec System 1002, Foss Tecator, Hilleroed, Denmark) and titration. Total lipids were extracted and quantified according to Folch et al, 1957 and using Folch solution (dichloromethane–methanol 2:1 v/v with 0.01% butylated hydroxytoluene—BHT) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximate composition analyses of the three olive tree leaf varieties were performed in triplicate, according to AOAC (2000, 2005, 2006) methods [ 32 , 33 , 34 , 35 ]: dry matter (in an oven at 105 °C to constant weight; P Selecta, Barcelona, Spain); ash (incinerated at 500 °C for 6h in a muffle furnace; Nabertherm B-180, Lilienthal, Germany); protein quantitation via the Kjeldahl method (AOAC, 2000) using a digestor (DK6 digester, Velp Scientific, Usmate, Italy) followed by distillation (Keltec System 1002, Foss Tecator, Hilleroed, Denmark) and titration. Total lipids were extracted and quantified according to Folch et al, 1957 and using Folch solution (dichloromethane–methanol 2:1 v/v with 0.01% butylated hydroxytoluene—BHT) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The water content of the leaves of O. europaea Cobrançosa, O. europaea Madural, and O. europaea Verdeal was determined from aqueous extracts through infrared hygrometry readings. The proximate compositions of the three varieties of samples were verified according to AOAC (2000,2005,2006) methods [32][33][34][35], drying the milled leaves at 105 • C to constant weight. Ash weight was determined via incineration at 500 • C. Total protein quantification was measured using the Kjeldahl method, while the total lipids were quantified according to Folch et al, 1957 and using Folch solution.…”
Section: Mineral Analysis Of the Selected Cultivarsmentioning
confidence: 99%
“…[7][8][9] The chemical components of AAF mainly include volatile oil, flavonoids, phenolic acids, organic acids, alkaloids, terpenes, and polysaccharides. [10][11][12] Our previous research showed a difference existed among aged AAF samples, but the specific different components were not clear. 13 AAF contains endogenous volatile and nonvolatile metabolite compounds, which constantly change during the aging process of AAF, and the use of advanced technology to study these endogenous compounds is relatively rare.…”
mentioning
confidence: 89%
“…A series of methods including HPLC fingerprinting [15], UPLC coupled with diode array detector MS (UPLC-DAD-MS) [16], GC-MS [17], and UPLC coupled with UV and quadrupole TOF-MS (UPLC-UV-Q-TOF-MS) [18] have been applied to qualitatively and quantitatively analyze the components in Artemisiae Argyi Folium. However, there are few comparative studies on the two medicinal materials.…”
Section: Introductionmentioning
confidence: 99%